Ligands can differentially and temporally modulate GPCR interaction with 14-3-3 isoforms - Haifeng Eishingdrelo; Xiaofa Qin; Luwa Yuan; Sathapana Kongsamut; Lei Yu (Elsevier, 2022)
GPCR signaling and function depend on their associated proteins and subcellular locations. Besides G-proteins and β-arrestins, 14-3-3 proteins participate in GPCR trafficking and signaling, and they connect a large number of diverse proteins to form signaling networks. Multiple 14-3-3 isoforms exist, and a GPCR can differentially interact with different 14-3-3 isoforms in response to agonist treatment. We found that some agonist-induced GPCR/14-3-3 signal intensities can rapidly decrease. We confirmed that this phenomenon of rapidly decreasing agonist-induced GPCR/14-3-3 signal intensity could also be paralleled with GPCR/β-arrestin-2 signals, indicating diminished levels of GPCR/signal adaptor complexes during endocytosis. The temporal signals could implicate either GPCR/14-3-3 complex dissociation or the complex undergoing a degradation process. Furthermore, we found that certain GPCR ligands can regulate GPCR/14-3-3 signals temporally, suggesting a new approach for GPCR drug development by modulating GPCR/14-3-3 signals temporally.